Electromechanical transient processes during supply voltage changing in the system of polymer insulation covering of the current-carrying core of ultra high voltage cables - Zolotaryov, V.M.; Shcherba, M.A.; Belyanin, R.V.; Mygushchenko, R.P; Korzhov, I.M. (Електротехніка і електромеханіка, 2018)
Aim. The article is devoted to the analysis of the electromechanical transient processes in a system of three frequency-controlled electric drives based on asynchronous motors that control current-carrying core motion, as well as to the study of the effect of such processes on the modes applying three-layer polymer insulation to the current-carrying core. Technique. The study was conducted based on the concepts of electromechanics, electromagnetic field theory, mathematical physics, mathematical modeling. Results. A mathematical model has been developed to analyze transients in an electromechanical system consisting of three frequency-controlled electric drives providing current-carrying core motion of ultra-high voltage cables in an inclined extrusion line. The coordination of the electromechanical parameters of the system drives has been carried out and the permissible changes in the supply voltage at the limiting mass while moving current-carrying core of ultra-high voltage cables with applied polymer insulation have been estimated. Scientific novelty. For the first time it is determined that with the limiting mass of the currentcarrying core, the electromechanical system allows to stabilize the current-carrying core speed with the required accuracy at short-term decreases in the supply voltage by no more than 27 % of its amplitude value. It is also shown that this system is resistant to short-term increases in voltage by 32 % for 0.2 s. Practical significance. Using the developed model, it is possible to calculate the change in the configuration and speed of the slack current-carrying core when applying polymer insulation, depending on the specific mass of the current-carrying core per unit length, its tension at the bottom, the torque of the traction motor and the supply voltage to achieve stable operation of the system and accurate working of the set parameters.